EDUCATION AND TRAINING An effective procedure skills training programme for GIM registrars. Issue 1 (2021) - Vijayakumar, Bavithra; Hynes, Gareth; Kitt, Jamie; Millette, Sarah; FitzPatrick, Michael
No abstract available